2018
DOI: 10.4103/ijd.ijd_143_18
|View full text |Cite
|
Sign up to set email alerts
|

A distinct clinicopathological presentation of cutaneous dermatophytosis mimicking autoimmune blistering disorder

Abstract: Infectious diseases can clinically present as vesiculobullous disorders. Direct immunofluorescence (DIF) study of skin biopsy helps distinguish true autoimmune blistering disorders from other conditions. In many situations, even DIF findings in infections disorders imitate autoimmune process. Here, we describe a case of 29-year-old female with extensive dermatophytosis having presentation mimicking bullous pemphigoid both clinically and histopathologically including DIF findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Bullous pemphigoid (BP), which manifests subepidermal skin lesions with bulla formation, is increasing in prevalence and has high mortality worldwide 2,3 . Evidence in recent years has indicated that BP is associated with malignancy, drugs, systemic lupus erythematosus, scleroderma, and psoriasis 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bullous pemphigoid (BP), which manifests subepidermal skin lesions with bulla formation, is increasing in prevalence and has high mortality worldwide 2,3 . Evidence in recent years has indicated that BP is associated with malignancy, drugs, systemic lupus erythematosus, scleroderma, and psoriasis 4 …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Evidence in recent years has indicated that BP is associated with malignancy, drugs, systemic lupus erythematosus, scleroderma, and psoriasis. 4 Antibodies against two hemidesmosome proteins of the dermal-epidermal junction, BP180 (collagen XVII) and BP230, might be the leading events in blister formation in BP. 5 Recent studies have also identified the important pathogenic mechanisms of IgE class autoantibodies in autoimmune skin diseases targeting BP180.…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the article, “A distinct clinicopathological presentation of cutaneous dermatophytosis mimicking autoimmune blistering disorder” which appeared in the Indian Journal of Dermatology, Issue 5, Volume 63. [1]…”
mentioning
confidence: 99%